The Impact of Artificial Intelligence on Corporate Law and Corporate Governance - Ahern, Deirdre (Cambridge University Press, 2022)
While affirming the robustness of core corporate law principles, this chapter explores how AI has, and could, impact the content, application and processes of corporate law and corporate governance, and the interactions of corporate law actors including boards, shareholders and regulators. As AI gains agency, the legal and cultural challenges in recognising robo-directors are probed. A contextual exploration of directors’ duties confronts the significant contemporary challenge concerning the need for directors to engage with AI’s potential to transform companies’ business models, culture and systems. When considering how and when to deploy AI applications, adoption and reliance upon AI by companies is considered against the backdrop of likely judicial application of key best interests duty and duty of care precepts to directors. The chapter also engages with corporate governance potential and controversies surrounding use of AI and robo-directors including stakeholder interests, board effectiveness, groupthink and internal biases.
The Cambridge Handbook of Private Law and Artificial Intelligence
Keywords: Distributed ledger technologies; Corporate law; Corporate governance; Directors’ duties; Artificial Intelligence; Digital Engagement; Digital Humanities; Identities in Transformation; International Integration; Smart & Sustainable Planet; Telecommunications; ARTIFICIAL INTELLIGENCE; Corporate Governance